STRATEGI PENGEMBANGAN TERNAK SAPI SISTEM KELOMPOK DI DESA NEGERI AGUNG KECAMATAN BUAY PEMUKA PELIUNG KABUPATEN OGAN KOMERING ULU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2018)
This research was conducted to find out the strategy of cattle development with group system at Negeri Agung District Buay Pemuka Peliung Ogan Komering Ulu Timur. This research has been conducted at Negeri District Negeri Agung Kecamatan Buay Pemuka Peliung, Regency of Ogan Komering Ulu Timur, Province Sumatera Selatan. Method used in this research is survey method that is research which take sample from a population and use questioner as data collecting tool. The sampling method used is stratified random sampling. To know the strategy of cattle development used SWOT analysis. Based on the analysis of internal strategy factors, it is found that the strength of the cattle business of the average group system is 2.92, while the analysis of external strategy factors shows an average of 3.15.